Comparative Study between Two Fractions of 9Gy & Three Fractions of 7Gy High Dose Rate Brachytherapy Following Concurrent Chemo Radiotherapy in Patients with Locally Advanced Carcinoma of Uterine Cervix (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Introduction: Traditionally, a judicious combination of external beam radiotherapy (EBRT) and intracavitary brachytherapy (ICBT) is the widely accepted primary modality of treatment for locally advanced carcinoma of the cervix. Although the recommendation ofAmerican Brachytherapy Society is